2019
DOI: 10.3390/nu11061303
|View full text |Cite
|
Sign up to set email alerts
|

Allium porrum Extract Decreases Effector Cell Degranulation and Modulates Airway Epithelial Cell Function

Abstract: Allium genus plants, such as leek (Allium porrum), are rich sources of anti-inflammatory and anti-oxidant secondary metabolites; this is of interest because it demonstrates their suitability as pharmacological alternatives for inflammatory processes, including allergy treatment. The composition of methanolic leek extract (LE) was analyzed by GC–MS and LC–IT/MS, and the total phenolic content and antioxidant capacity were quantified by colorimetric methods. Its pharmacological potential was analyzed in human br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Moreover, leek has been shown to decrease the risk of different cancers [ 9 , 10 ]. Furthermore, the extracts of Allium ampeloprasum show antiallergic and anti-inflammatory effects [ 11 ]. Leek has also been found to exhibit antimicrobial properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, leek has been shown to decrease the risk of different cancers [ 9 , 10 ]. Furthermore, the extracts of Allium ampeloprasum show antiallergic and anti-inflammatory effects [ 11 ]. Leek has also been found to exhibit antimicrobial properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leek leaf extract (LLE), according to Ibrahim and Kenawy (2017) [37], has potent anthelmintic action and can be used to eradicate or inactivate fish infections caused by metacercarial parasites. [38] also demonstrated that leek extract can suppress immunological and non-immunological stimuli that may help stabilize mast cells in allergic reactions. The consumption of Allium could also reduce cardiac problems in future [39].…”
Section: Table 1: Nutritional and Therapeutic Potential Of Leekmentioning
confidence: 93%
“…Extracts were produced differently for each vegetables: the leaves and roots of Tanabe radish and Moriguchi radish, the leaves of bunching onion (Allium fistulosum), and the fruit of mizu eggplant. anti-allergic effects [9]. Therefore, this inhibitory effect is not a characteristic of bunching onion.…”
Section: Osakan Traditional Vegetables With Potential Anti-allergic A...mentioning
confidence: 95%